The Social Responsibility among Higher Education Students - Emese Beáta Berei (MDPI AG, 2020)
The aim of this research is to emphasize the importance of education for the philanthropic responsibilities of students. The basic term of the explanatory research is corporate social responsibility, adapted for higher education institutions—the philanthropic responsibilities of students, their implication on charity organization memberships or volunteering activities, and their motivation to help others. Special attention was given to the following questions: Are students involved in charity organization activities or voluntary work? Are there any differences between state and private universities regarding the philanthropic activities of students? How frequently, where, and why are they involved in volunteering? What is the latent structure of students‘ motivations? The quantitative international survey dates were collected by the Centre for Higher Education Research and Development from Debrecen University, Hungary, and the present examination focuses on the sample from Romania. Using Statistical Package for the Social Sciences (SPSS) statistical software, first, through a longitudinal perspective, Romanian students’ implications from state and private institutions were compared. Second, the paper analyzes the characteristics of volunteering and student’s motivations. The conclusions present significant differences between state and private institutions. Students traditional motivations, i.e. to help others, were very common and connected with relational and self-development intentions. This mixed motivational factor was different from the global motivational factor (to learn new languages and to discover new cultures).